Strengthening Responsible Journalism Through Self-Efficacious Learning-Oriented Media Literacy Interventions - Auksė Balčytienė (Media and Communication)
This article investigates the challenges journalism professionals face in a rapidly changing digital media environment, proposing that a “processual” and human-centered perspective might offer valuable insights into developing resilient professionalism. The article builds its argument on theories of transmediality and hybridization in digital media ecosystems and the socio-psychological development toward accountable communication and responsible professionalism. It specifically looks at future journalists as active learners to whom media literacy interventions may offer new insights into the mental processes in professional decision-making. It tests these ideas in an experimental study with journalism students, where the lateral reading approach was applied within the framework of learning skills for information verification. Results from the thematic analysis of students’ reflexive assessments of their practice reveal norms illustrative of a self-efficacious learning process: Students’ answers demonstrate empowering and perseverance-directed approaches. As argued, these norms are geared toward imposing a higher media awareness and self-regulatory capacity, which is critical for accountable decision-making in transmedial and highly interactive digital information environments.